Motivational and Success Factors of Agripreneurs: Insights from Andhra Pradesh and Telangana - Guttikonda, Aneeja; N. Sivaramane; R. Sivaprasad; B. Ganesh Kumar (Journal of Agricultural Extension Management, 2025)
The research study explores the motivational factors, and success strategies of agripreneurs in the study area i.e., Andhra Pradesh and Telangana. With a sample size of 34 respondents, the study delves into the demographic distribution, investment preferences, marketing strategies, and sources of funding for agricultural entrepreneurs. Key findings indicate a predominance of male agripreneurs, a preference for single production activity, and significant reliance on seed funds from individuals and grants from the government. This paper also highlights the importance of strategic location, infrastructure investment, and effective networking for entrepreneurial success in agripreneurship. The study underscores the vital role of agripreneurship in promoting rural development, food security, and economic sustainability in India